2003
DOI: 10.1093/emboj/cdg032
|View full text |Cite
|
Sign up to set email alerts
|

Absence epilepsy and sinus dysrhythmia in mice lacking the pacemaker channel HCN2

Abstract: Hyperpolarization-activated cation (HCN) channels are believed to be involved in the generation of cardiac pacemaker depolarizations as well as in the control of neuronal excitability and plasticity. The contributions of the four individual HCN channel isoforms (HCN1±4) to these diverse functions are not known. Here we show that HCN2-de®cient mice exhibit spontaneous absence seizures. The thalamocortical relay neurons of these mice displayed a near complete loss of the HCN current, resulting in a pronounced hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
502
6
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 486 publications
(555 citation statements)
references
References 41 publications
(59 reference statements)
38
502
6
5
Order By: Relevance
“…1). The HCN1 and HCN2 antibodies labeled broad bands with a molecular mass of 120 kDa consistent with the previous studies (Lorincz et al, 2002;Ludwig et al, 2003). The HCN3 and HCN4 antibodies gave rise to broad bands around molecular masses of 85 and 140 kDa, respectively, which are consistent with the previous study (Muller et al, 2003).…”
Section: Antibody Specificitysupporting
confidence: 91%
See 3 more Smart Citations
“…1). The HCN1 and HCN2 antibodies labeled broad bands with a molecular mass of 120 kDa consistent with the previous studies (Lorincz et al, 2002;Ludwig et al, 2003). The HCN3 and HCN4 antibodies gave rise to broad bands around molecular masses of 85 and 140 kDa, respectively, which are consistent with the previous study (Muller et al, 2003).…”
Section: Antibody Specificitysupporting
confidence: 91%
“…The HCN4 mRNA is strongly expressed in the mitral cell layer of the olfactory bulb, anterodorsal, laterodorsal, ventroposterior nuclei of the thalamus, and medial habenular nucleus (Monteggia et al, 2000;Santoro et al, 2000;Ludwig et al, 2003). Consistent with these studies, we found very 32 intense HCN4-LI in the thalamic nuclei, but not in the mitral cell layer and medial habenular nucleus.…”
Section: Correlation Between Localization Of Hcn Mrnas and Hcn-lissupporting
confidence: 90%
See 2 more Smart Citations
“…In mice, deletion of the HCN2 subunit produces animals with 5-Hz spike-and-wave discharges and absence-like seizures. 163 The WAG/Rij rat model of ab-sence epilepsy shows a loss of HCN1 function in the cortex 164 (possibly linked to the origin of cortical spikeand-wave discharges) but enhanced HCN1 expression in the thalamus. 165 In addition, changes in I h and in HCN subunit expression have been observed in epileptogenesis.…”
Section: Hcn Channelsmentioning
confidence: 99%